Genome analysis of Bifidobacterium adolescentis and investigation of its effects on inflammation and intestinal barrier function - Li, Bo; Wang, Haoyu; Wang, Mengmeng; Liang, Hewei; Hu, Tongyuan; Yang, Jinlong; Li, Shangyong; You, Xinbi; Xia, Binbin; Yuan, Yue; Zou, Yuanqiang; Miao, Yinglei; et al. (Frontiers in Microbiology, 2025)
Numerous studies have confirmed that gut microbiota is a key driver in the occurrence and progression of inflammatory bowel disease (IBD). Based on the bacterial collection constructed in our previous studies, we founded that Bifidobacterium adolescentis AF91-08b2A has the potential beneficial function. We designed cohort studies, genomic studies and animal experiments to further explore the probiotic function of Bifidobacterium adolescentis AF91-08b2A and its therapeutic effect on IBD. The depletion of B. adolescentis in individuals with IBD suggested its significance for intestinal health. Genomic analysis highlighted the probiotic attributes of B. adolescentis AF91-08b2A, including resistance to antibiotics and stress, and metabolic pathways related to energy and carbohydrate metabolism, which are likely to enhance its therapeutic efficacy. In DSS-induced mice colitis model, the strain significantly enhanced the disease activity index (DAI), curbed weight loss, and attenuated colonic damage. It effectively modulated the immune response by reducing the levels of pro-inflammatory cytokines such as IL-6, IL-1β, IL-17A, IFN-γ, and TNF-α, while promoting the secretion of anti-inflammatory cytokines like IL-4, IL-10, and TGF-β1. The restoration of tight junction proteins ZO-1, occludin, and claudin-2 by B. adolescentis AF91-08b2A demonstrated its capacity to safeguard the intestinal epithelial barrier. Collectively, our findings indicate B. adolescentis AF91-08b2A as a valuable therapeutic option for UC, with its multifaceted approach to reducing inflammation and fortifying the intestinal barrier.